Program “EARS” Sebagai Upaya Peningkatan Psychological Well Being Pada Masa Pendemi Covid 19 - Zakariyya, Farhan; Kosasih, Engkos; Damayanti, Lira Fessia; Musthofa, Muhammad Ariez; Kosasih, Ismawati; Akhlan, Riksma Nurahmi Rinalti (Program Studi Psikologi Universitas Pendidikan Indonesia, 2022)
Abstract The EARS program is based on the Psychological First Aid (PFA) concept to improve sychological well-being. The program is carried out online using the WhatsApp chat media, training conducted by the helper who received the training. The subjects in this study were adolescents aged 19-25 years who registered and filled out informed consent. Subjects totaling 30 people, but who filled out a total of 13 people in the test so that only 13 people were processed the data. This study uses a quasi-experimental one group pretest and posttest design. Data analysis used Paired sample T-Test with P under 0.05. This shows that the EARS Program can improve psychological well-being.Keywords: pandemi, psychological wellbeing, psychology first aid, student Abstrak Program EARS disusun berdasarkan konsep Psychological First Aid (PFA) untuk dapat meningkatkan psychological well-being. Program di lakukan secara online dengan menggunakan media chat whatsapp yang dilakukan oleh helper yang mendapatkan pelatihan. Subjek dalam penelitian ini adalah remaja usia 19-25 tahun yang mendaftarkan diri dan mengisi informed consent. Subjek berjumlah 30 orang namun yang mengisi keseluruhan test 13 orang sehingga hanya 13 orang yang di olah datanya. Penelitian ini menggunakan desain kuasi eksperimen one group pretest and posttest design. Analisis data menggunakan paired sample T-Test dengan hasil P dibawah 0,05. Hal ini menunjukan Program EARS dapat meningkatkan psychological well-being. Kata kunci: kesejahteraan psikologis, mahasiswa, pandemi, psikologi pertolongan pertama